2019
DOI: 10.1021/acs.langmuir.9b02431
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Fluoroquinolone Antibiotics at the Gas–Liquid Interface Using Ionic Surfactants

Abstract: The overuse of antibiotics in today's society has resulted in high concentrations of pharmaceutical contaminants in the natural environment. In this work, we investigated the surfactant-mediated adsorption of fluoroquinolone (FQ) antibiotics at the gas−liquid interface and their separation using a semi-batch foam fractionation process. FQs being a zwitterionic compound have an affinity to bind with both cationic and anionic surfactants. The adsorption of FQs to the gas−liquid interface was investigated using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…CTAB electrostatically interacts with the charged headgroup of short-chain PFAS, while the hydrophobic tail of CTAB interacts with the hydrophobic tails of PFAAs, resulting in an increased level of accumulation of the short chains at the plasma−liquid interface, exposing these compounds to the reactive species formed by the plasma. 17,18 In these experiments, the concentration of PFHxA decreased to below detection limits within 30 min, the concentrations of PFPeS and PFPeA were <50 ng/L after 60 min, the concentration of PFBA was <50 ng/L after 120 min, and the PFBS concentration reached a final concentration of 100 ng/L after 120 min (Figure 6). Overall, the total short-chain PFAA concentration was decreased by 88% in 120 min.…”
Section: Resultsmentioning
confidence: 76%
“…CTAB electrostatically interacts with the charged headgroup of short-chain PFAS, while the hydrophobic tail of CTAB interacts with the hydrophobic tails of PFAAs, resulting in an increased level of accumulation of the short chains at the plasma−liquid interface, exposing these compounds to the reactive species formed by the plasma. 17,18 In these experiments, the concentration of PFHxA decreased to below detection limits within 30 min, the concentrations of PFPeS and PFPeA were <50 ng/L after 60 min, the concentration of PFBA was <50 ng/L after 120 min, and the PFBS concentration reached a final concentration of 100 ng/L after 120 min (Figure 6). Overall, the total short-chain PFAA concentration was decreased by 88% in 120 min.…”
Section: Resultsmentioning
confidence: 76%
“…The results indicate that [C 10 mim][BF 4 ] has more binding affinity with the drug owing to the presence of four highly electronegative fluorine atoms involved in attraction with the carboxylic and carbonyl moieties of CIP. Similar results have been proposed by Ghosh et al for the interaction of CIP with surfactants SDS and CTAB, and they agreed that electrostatic attraction plays a vital role in the interaction between CIP and SDS/CTAB molecules in aqueous medium . The associated interaction parameters for all of the IL–CIP interactions are summarized in Table , and they revealed that the binding processes are spontaneous in nature and entropy-driven.…”
Section: Resultsmentioning
confidence: 99%
“…56 and CTAB, and they agreed that electrostatic attraction plays a vital role in the interaction between CIP and SDS/CTAB molecules in aqueous medium. 39 The associated interaction parameters for all of the IL−CIP interactions are summarized in Table 2, and they revealed that the binding processes are spontaneous in nature and entropy-driven. The change in enthalpy and entropy values signifies that the bimolecular interaction between the drug and ILs is enthalpy−entropydependent.…”
Section: Time-resolved Fluorescence Decay Studiesmentioning
confidence: 99%
See 2 more Smart Citations